خصخصة السجون - منصور, شلاهبية; حيزوم بدر الدين, مرغني (University of Eloued جامعة الوادي, 2020)
لقد كان للتحولات العالمية التي شهدها المجتمع الدولي وخصوصا في ظل تغول الفكر الرأسمالي بالغ الأثر في إعادة النظر في كل المسلمات القانونية والأمنية التي تقوم عليها الاستراتيجيات الوطنية، من خلال خصخصة السجون العامة التي كانت تديرها الدولة حصرا والاستعانة بالقطاع الخاص كبديل ملائم تسند إليه بعض المهام بضوابط قانونية محددة مسبقا، فرضتها مجموعة من العوامل والأسباب التي دفعت نحو التوجه للخصخصة أهمها الزيادة الكبيرة في عدد السجناء والاكتظاظ داخل السجون، واحجام الدول عن تخصيص الأموال لبناء سجون جديدة وخصوصا مع الأزمات الاقتصادية المتعاقبة، يضاف لها زيادة احتجاز المهاجرين غير النظامين وخصوصا في الولايات المتحدة وأروبا، والاحتياجات المتوقعة في زمن الأزمات. أخيرا زيادة الضغوطات التي تمارسها الشركات الأمنية الخاصة بهدف الحصول على مزيد من العقود الحكومية لإدارة السجون المخصخصة. Global transformations witnessed by the international community, especially in light of the deception of capitalist thought, had a major effect of reconsidering all legal and security postulates on which national strategies are based, through the privatization of public prisons that were administered exclusively by the state and the use of the private sector as an appropriate alternative. The private sector was assigned some tasks with pre-defined legal controls imposed by a set of factors and reasons that pushed towards privatization. The most important of these factors are the large increase in the number of prisoners, overcrowding inside prisons, and the reluctance of countries to allocate funds to build new prisons, especially with successive economic crises. This is in addition to the increased detention of illegal immigrants, especially in the United States and Europe, the anticipated needs in times of crisis, and finally the increase in the pressure exerted by private 17311011721852020 security companies in order to obtain more government contracts for the management of privatized prisons.
مجلد11، عدد1
Keywords: الخصخصة، السجون، مراكز الاحتجاز، القانون، الشركات الأمنية; privatization, prisons; detention; centres; the law; security companies